MUHAMMAD SA’ID AL-‘ASHMAWI (Mencabar Pemikirannya tentang Penerapan Syarî’ah di Mesir) - Moh. Hefni (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
The rise of a vigorous and sometimes violent Islamistmovement in Egypt has attracted considerable attentionfrom scholars. Less attention has been given to those whohave responded to this challenge at the level of ideologicaldebate. One of these is a prominent judge, Muhammad Sa’idal-‘Ashmawi. He argues that the call for the